Adaptive prestressing system using shape memory alloys and conventional steel for concrete crossties. (10th May 2021) - Sung, Minsoo; Andrawes, Bassem
Abstract: Typical railroad concrete crossties are prestressed with straight high strength steel (HSS) reinforcement throughout the length of the tie, which could lead to end splitting cracks and excessive stress concentration at compressive zones. This paper presents a novel adaptive prestressing system (APS) that can apply localized prestressing only at targeted regions. The APS comprises a short fuse made of shape memory alloy (SMA) connected to HSS reinforcement and placed at the location where prestressing is needed. Once the SMA fuse is thermally activated, recovery stress is induced in the system applying internal prestressing force at the desired locations. The new APS is investigated experimentally through testing a half-scale crosstie specimen prestressed with APS. Finite element analysis is also conducted to compare the behavior of APS and HSS reinforced crossties while considering prestress losses in both systems. The study results indicate that APS is able to effectively apply prestress at target regions as designed with significantly less prestress losses compared to HSS.